Canadian state trials. - Greenwood, F. Murray (Frank Murray), 1935-; Wright, Barry, 1957- (Osgoode Society for Canadian Legal History series., 1996)
This volume examines this record of Canadian state trials for the period 1608-1837, highlighting security law during the American revolution, the wars against revolutionary/Napoleonic France, and the War of 1812.